Parenting with PTSD: A Review of Research on the Influence of PTSD on Parent-Child Functioning in Military and Veteran Families - Creech, Suzannah K.; Misca, Gabriela (Frontiers in Psychology, 2017)
Posttraumatic stress disorder (PTSD) is strongly associated with exposure to war related trauma in military and veteran populations. In growing recognition that PTSD may influence and be influenced by social support and family systems, research has begun to explore the effects that war related trauma and the ensuing PTSD may have on varied aspects of close relationship and family functioning. Far less research, however, has examined the influence of war-related PTSD on parent-child functioning in this population. This paper provides a timely review of emergent literature to examine the impacts that PTSD may have on parenting behaviors and children’s outcomes with a focus on studies of military and veterans of international conflicts since post-9/11. The review sheds light on the pathways through which PTSD may impact parent-child relationships, and proposes the cognitive-behavioral interpersonal theory of PTSD as a theoretical formulation and extends this to parenting/children. The review identifies the strengths and limitations in the extant research and proposes directions for future research and methodological practice to better capture the complex interplay of PTSD and parenting in military and veteran families.